2015
DOI: 10.1007/s00240-015-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive percutaneous nephrolithotomy: an effective treatment for kidney stones in infants under 1 year of age. A single-center experience

Abstract: We aimed to present the outcomes of PNL surgery performed in infantile patients with small renal stones who were younger than 1 year of age. A single-center prospective trial was initiated and during the period between Jan 2013 and Jan 2015, PNL was applied to 20 renal units of 16 infants (6 girls and 10 boys), including 4 patients with bilateral kidney stones. PNL was performed in patients with renal stones larger than 2 cm, as well as stones resistant to SWL or renal stones that were undetectable during SWL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
1
2
1
Order By: Relevance
“…Our SFR results are comparable to a study conducted in Bangalore in 2021, in which they reported their experience of minimally invasive PCNL in 24 infants, achieving an SFR of 91% ( 25 ). Our SFR results are higher than the study conducted by Dağgülli et al and Bodakci et al in which SFR results were 80% and 81.2%, respectively ( 18 , 26 ). A similar study was conducted in USA by Jackman et al who performed PCNL in eleven infants and preschool children using 11 Fr peel away sheath.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Our SFR results are comparable to a study conducted in Bangalore in 2021, in which they reported their experience of minimally invasive PCNL in 24 infants, achieving an SFR of 91% ( 25 ). Our SFR results are higher than the study conducted by Dağgülli et al and Bodakci et al in which SFR results were 80% and 81.2%, respectively ( 18 , 26 ). A similar study was conducted in USA by Jackman et al who performed PCNL in eleven infants and preschool children using 11 Fr peel away sheath.…”
Section: Discussioncontrasting
confidence: 89%
“…The overall complication rate in our study is comparable to the study done in Bangalore by Patil et al, which is 16% ( 25 ). However, our complication rate is relatively better than that reported by Dağgülli et al, which was 40%, including bleeding requiring blood transfusion in 10%, fever in 10%, and UTI in 20% of the patients ( 18 ). Our complication rate is also better than that of Bodakci et al, which was 27%, including bleeding requiring blood transfusion in 4.2%, fever in 8.3%, and UTI in 14.6% of the patients ( 26 ).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Minimal invaziv yöntemlerin 1 yaş altı infantlarda PNL'nin güvenilir uygulanabilmesine imkân tanıdığını belirten Dağgülli ve ark. yapmış oldukları başka bir çalışmada en küçüğü 5 aylık ve yaş ortalaması 9,5 ay olan 1 yaş altı 16 infantta (toplam 20 ünite) 5 hastaya 20 Fr, 15 hastaya 14 Fr dilatasyon yaparak uyguladıkları prosedürde tek seansta %80 başarı elde ettiklerini belirtmiştir (17). Dede ve ark.…”
Section: Discussionunclassified